Incidence of Fasciolosis in Animals slaughtered Between 1998-2000 in Slaughterhouse of Elazığ ELET Company and Its Economic Significance - Kaplan, Mustafa; Kuk, Salih; Kalkan, Ahmet (Fırat University, 2002)
Aim: This study was designed in order to find out the year-by-year distribution of fasciolosis prevalence in animals that were slaughtered in slaughterhouse of Elazığ ELET Company between January 1, 1998 and December 31, 2000 and to figure out the dimensions of economic loss because of this condition. Meterial and Methods: Yearly prevalence of fasciolosis in cows, sheep and goats slaughtered during the above stated period has been detected from the veterinary registration books of the ELET Company. The calculated economic loss caused by fasciolosis was based on the wholesale prices of the company. Results: Fasciolosis was present in 1.368 of 6.1157 cows (2.23%), in 1.740 of 82.250 sheep (2.11 %) and in 766 of 54.700 goats (1.40%). 3.874 of a total number of 198.107 animals (1.95%) were determined to have fasciolosis. Total value of livers in animals with fasciolosis was 21.428.000.000 TL. Conclusion: 3874 animals were detected with fasciolosis in only one slaughterhouse in our province during a three year period and yearly average economic losses related to this condition is 7.142.000.000 TL. Preventive measures should be implemented in order to decrease the incidence of fasciolosis in animals and to minimize the economic losses related to this condition.

Amaç: Bu çalışma 1 Ocak 1998-31 Aralık 2000 tarihleri arasında Elazığ ELET AŞ. Kesimhane'sinde kesilen kasaplık hayvanlarda görülen fasciolosisin yıllara göre dağılımını ve bu nedenle oluşan ekonomik kayıpların boyutunu araştırmak amacıyla yapıldı. Gereç ve Yöntem: Kurumun veteriner hekim kayıt defterleri incelenerek bu dönemde kesimi yapılan sığır, koyun ve keçilerde fasciolosis görülme sıklığı yıllara göre irdelendi. Kurum toptan satış fiyatları temel alınarak bu dönemdeki fasciolosise bağlı ekonomik kayıplar hesaplandı. Bulgular: Bu üç yıllık dönemde kesimi yapılan 61.157 sığırdan 1368'nde (%2.23), 82.250 koyundan 1.740'ında (%2.11) ve 54.700 keçiden 766'sında (%1.40) fasciolosis saptandı. Toplam olarak kesimi yapılan 198.107 hayvanın 3.874'ünde (%1.95) fasciolosis saptandı. Fasciolosis nedeniyle imha edilen karaciğerlerin toplam ekonomik değeri 21.428.000.000 TL olarak hesaplandı. Sonuç: İlimizde tek bir kesimhanede 3 yıllık sürede toplam 3874 fasciolosisli hayvan saptandığı ve buna bağlı yıllık ortalama ekonomik kaybın 7.142.000.000 TL olduğu görülmüştür. Hayvanlardaki fasciolosis yaygınlığının azaltılması ve ekonomik kayıpların asgari düzeye çekilebilmesi için önlemler alınması gerekli görülmektedir.
Elazığ ELET A.Ş. Kesimhanesinde 1998-2000 Yılları Arasında Kesilen Hayvanlarda Fasciolosis Görülme Sıklığı